Răspuns :
a)
[tex](( \frac{2}{5} ) {}^{2} ) {}^{x} = ( \frac{4}{10} ) {}^{6} \\ \\ (\frac{2}{5} ) {}^{2x} = ( \frac{2}{5} ) {}^{6} \\ \\ 2x = 6 \\ x = 3[/tex]
b)
[tex]( \frac{1}{9} ) {}^{x} \times ( \frac{1}{9} ) {}^{5} = ( \frac{2}{18} ) { }^{10} \\ \\ ( \frac{1}{9} ) {}^{x + 5} = ( \frac{1}{9} ) {}^{10} \\ \\ x + 5 = 10 \\ x = 5[/tex]
c)
[tex]( \frac{3}{7} ) {}^{x} \div ( \frac{6}{14} ) {}^{3} = ( \frac{15}{35} ) {}^{2} \\ \\ ( \frac{3}{7} ) {}^{x} \div ( \frac{3}{7} ) {}^{3} = ( \frac{3}{7} ) {}^{2} \\ \\ ( \frac{3}{7} ) {}^{x - 3} = ( \frac{3}{7} ) {}^{2} \\ \\ x - 3 = 2 \\ x = 5[/tex]